Моделирование территориальной организации водопользования на примере феодосийского регионального водного бассейна - Лукьянова, М.Ю.; Ковальчук, А.Н.; Наурзоков, Ю.Х. (Культура народов Причерноморья, 2013)
Вперше застосований принцип інтегрованого управління до територій з обмеженими
природними водними ресурсами та інтенсивним природокористуванням. Модель територіальної
організації водокористування розроблена на основі теорії графів і представлена деревом зв'язків, в
основу якого покладені векторні показники напрямку та об'ємно-швидкісних характеристик поверхневих
і підземних водотоків.
Ключові слова: територіальна організація водокористування, водний басейн, математична модель,
поверхневі і підземні водні Впервые применен принцип интегрированного управления к территориям с ограниченными
природными водными ресурсами и интенсивным природопользованием. Модель территориальной
организации водопользования разработана на основе теории графов и представлена деревом связей, в
основу которого положены векторные показатели направления и объемно-скоростных характеристик
поверхностных и подземных водотоков.
Ключевые слова: территориальная организация водопользования, водный бассейн, математическая
модель, поверхностные и подземные водные ресурсы. Integrative management of water resources on the base of hydrographic principle, which is most,
concerned large river basins, admitted as most effective way of territory water problems decision in the world
practice. But the question of ecosystems and biodiversity preserving, of quality drinking water sustainable
reproducing are concerned substantially, of rational water using managing functions integration in the
conditions of limited territorial water resources. Application of integrative management principle for territories
with limited natural water resources, unsustainable network of surface and underground water sources, and
with intensive industrial-economy activities at the same time, was firstly proposed in this work. Principles of
optimization of natural-anthropogenic systems structure laid into the base of proposed model of water-using
territorial organization. Using of discrete mathematics methods, namely graphs theory, proposed to
mathematics description of object-functional ties of different nature discrete object, in particular of water
sources. Model of water-using territorial organization is shown here as “ties tree”; vector indexes of direction
and volume-speed characteristics of surface and underground water-drains laid into the base of this ” tree”.
Vectors of condition of natural reserves of basin water resources and donor basin resources describes positive
compilation part of water balance of considering territory. Involving of water resources into economic activity is
describing by bloc of water resources conditions, which are involved into producing from each source to each
consumer. Models have to be limited for this bloc, because consuming water volume does not have to be higher
than volume water, supplying to consumers. From other side, abundance of supplying water has both ecological
and economy-social consequences. In the first case this factor has an effect upon ecological safety of the whole
region, and in second it connected with not normally high economic load to consumers. Algorithm of modeling
for each bloc of system contains definition of model objects, definition of multi-object ties and its normalizing.
The proposed model used by us for determine of functions of water moving in natural and anthropogenic
channels of Feodosia regional water basin. As it was emphasized in this work, using of proposed mathematics
method can be taken for modeling of system of connection between objects of different nature. In particular,
registration of polluting matters transferring in downpour and housekeeping drains, and registration of its
concentration and changing of it on its way to consumer is very interesting process.
Keywords: territory organizing of water-using, water basin, mathematics model, surface and underground
water resources.